The Effectiveness Of Ning Yaonah Service Innovation For Population Administration In Jombang Regency - Sari, Dwi Anita Maretika; Mustofa, Amirul (Socious Journal, 2025)
The purpose of the research is to evaluate the effectiveness of Ning Yaonah service innovation in the process of managing administrative services, both in terms of benefits felt by the community and the challenges faced in its implementation. This study uses qualitative research. The location of the research was carried out at the Population and Civil Registration Office of Jombang Regency. The data collection methods used include literature studies, and document data. The results of the study are that Ning Yaonah service innovation has proven effective in improving the quality and efficiency of population administration services and obtaining an “A” predicate qualification in Jombang Regency. The program has succeeded in creating a transparent and accountable service, by providing easy access and simple procedures. Practical Implications Increasing the accessibility and efficiency of population administration services through digitalization, so that people can take care of documents easily and quickly without long queues